ESTUDIO PREVIO DE ALGUNOS ASPECTOS DEL PROCESO VERBAL Y SUGERENCIAS PARA SU REFORMA - Bejarano Guzmán, Ramiro (Revistas ICDP, 2015)
ESTUDIO PREVIO DE ALGUNOS ASPECTOS DEL PROCESO VERBAL Y SUGERENCIAS PARA SU REFORMA